Capability, social capital and opportunity-driven graduate entrepreneurship in Tanzania - Wakkee, Ingrid; Hoestenberghe, Karel; Mwasalwiba, Ernest (Journal of Small Business and Enterprise Development, 2024)
Purpose The purpose of this paper is to gain insight into the reasons why most Tanzanian graduates do not consider entrepreneurship as an attractive career option despite dire labor market conditions, while a small number of them are able to benefit from local opportunities.